Hubungan Gaya Kognitif Siswa Dengan Kemampuan Pemecahan Masalah Matematika - Adrian Patingki; Abdul Djabar Mohidin; Resmawan Resmawan (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
This article discusses the relationship between students' cognitive style and mathematical problem-solving abilities in the number pattern material carried out at SMP Negeri 1 Botupingge in the odd semester of the 2021/2022 academic year. The research method used is a survey method with a correlational approach, with a questionnaire instrument to determine students' cognitive style and problem-solving tests to measure students' mathematical problem-solving abilities. The results showed that the correlation coefficient between students' cognitive styles and mathematical problem-solving abilities was 0.60, which means that there is a relationship between students' cognitive styles and mathematical problem-solving abilities at a high level. The coefficient of determination of 0.36 indicates that 36% of the contribution of cognitive style to the improvement of mathematical problem-solving abilities, and the remaining 64% is determined by other factors.